Understanding Literature Reviews: Types, Methodologies, and Applications - Michael Willie (Golden Ratio of Mapping Idea and Literature Format, 2026)
Literature reviews are integral to academic research, providing synthesised insights into existing knowledge while identifying gaps for future exploration. This paper explores various types of literature reviews, including narrative, systematic, meta-analyses, scoping, critical, and integrative reviews. Each type is characterised by distinct methodologies and purposes, ranging from providing broad overviews to rigorous synthesis of evidence and quantitative data analysis. Understanding these methodologies aids researchers in selecting appropriate review methods tailored to their research questions, thereby enhancing the quality and impact of their work across disciplines.